Skema Transfer Pricing Pada Perusahaan Pertambangan dan Faktor-Faktor yang Terlibat - Suparno, Suparno; Sawarjuwono, Tjiptohadi (E-Jurnal Akuntansi; Vol 29 No 2 (2019), 2019)
The purposes of this study are to analyze and describe the tax avoidance schemes through transfer pricing and the factors that influence the decision on transfer pricing by mining companies. Data analysis uses qualitative techniques with qualitative data obtained from literature studies from internet sources. The results of the study shows that the transfer pricing schemes carried out by mining companies in general can be divided into two, namely by transferring mining rights to other companies that have special relationships and conducting transactions with companies that have special relationships, with prices agreed to be below the average market price. The results of the study also indicate that the mining company's decision to transfer pricing is influenced by nine factors, namely executive characteristics, leverage, scale of the company as a multinational company, disclosure of social responsibility, capital intensity, institutional ownership, audit committee, audit quality, and information transparency. Keywords : Transfer Pricing, Tax Avoidance, Mining Companies.